Elementos regulatórios responsáveis pelo controle da estabilidade do mRNA de alfa tubulina de Trypanosoma cruzi - Patricia Rosa de Araujo (2007)
alpha/beta-tubulin mRNAs expression in T.cruzi is under an auto-regulatory control that affects these transcript half-lives during the parasite life cycle. Whereas epimastigotes present high levels of tubulin mRNAs, an excess of free tubulin monomers is correlated to a decrease in tubulin mRNA levels in amastigotes. This reduction is not a result of changes in transcription; instead, it is due to a reduction in and tubulin mRNA half-lives. By incubating epimastigotes with vinblastine (a microtubule depolymerization inducer) we have observed an inverse correlation between free tubulin and mRNA stabilization. Transient transfection assays have indicated that the 3UTR and the first four aminoacids of the -tubulin might be involved in mRNA destabilization. Therefore, the aim of this work is to further investigate the role of 3UTR of the -tubulin mRNA (and more precisely, the AU-rich element present within this region) on the control of mRNA abundance. Stably transfected epimastigotes with plasmids containing the wild-type or ARE-deleted -tubulin 3UTR downstream the luciferase reporter gene were generated. Our results suggest that, similar to tubulin expression in amastigotes, luciferase mRNA containing the deleted element is less abundant and less stable in epimastigotes when compared to the mRNA containing the wild-type 3UTR. Sequences present in the -tubulin 3UTR however, do not interfere with the destabilization of -tubulin mRNA in response to vinblastine treatment. These findings indicate that differently from other AREs found in trypanosomatids, which cause degradation of mRNAs, the -tubulin ARE is an stabilizing element responsible for maintaining high levels of -tubulin mRNA in epimastigotes. We are currently investigating the role of -tubulin 5UTR and coding sequences as well as possible interactions between regulatory trans-acting factors and ARE-binding domain on -tubulin mRNA stability